Immersion time of gutta percha points in various concentrations of zephiran chloride - Fran, Grace Marie
The optimum immersion time of gutta percha points in various concentrations of zephiran chloride as a disinfecting solution was investigated for the maintenance of the chain of asepsis during obturation of the root canal.